2017
DOI: 10.1093/occmed/kqx169
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in limited duty time for lower limb injury

Abstract: The substantial amount of limited duty for lower limb musculoskeletal injuries among soldiers highlights the need for improvement in training-related injury screening, prevention and timely treatment with particular attention to knee injuries. The excessive impact of lower limb injuries on female soldiers' occupational functions should be a surveillance priority in the current environment of expanding gender-integrated training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Many studies included in this analysis and in general specify the ankle as the most commonly injured location of the distal lower extremity 4 23 30 37 38 61 92–95. However, some studies17 29 59 60 66 67 81 91 localise the majority of these injuries to the foot, contrasting with this study’s findings that acute ankle injuries are the most common type of injuries to the distal lower extremity during military training. This seemingly contradicting finding can be explained by the fact that all but one of the articles91 citing the foot as the most commonly injured location are studies primarily focused on stress fractures or overuse injuries.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Many studies included in this analysis and in general specify the ankle as the most commonly injured location of the distal lower extremity 4 23 30 37 38 61 92–95. However, some studies17 29 59 60 66 67 81 91 localise the majority of these injuries to the foot, contrasting with this study’s findings that acute ankle injuries are the most common type of injuries to the distal lower extremity during military training. This seemingly contradicting finding can be explained by the fact that all but one of the articles91 citing the foot as the most commonly injured location are studies primarily focused on stress fractures or overuse injuries.…”
Section: Discussionmentioning
confidence: 78%
“…Forty-two studies were level II evidence 1 3 4 9 11 18–54. Forty-two studies were level III,2 5–8 10 12 54–89 and 2 studies were level IV 90 91. While assessing study size, we found that 85 (93%) studies included over 120 subjects; 4 (4%) studies included between 40 and 120 subjects; and only 2 (3%) studies included fewer than 40 subjects.…”
Section: Resultsmentioning
confidence: 84%
“…When considering an injury risk in active duty military personnel, we may bias our thinking toward combat-related tasks involving heavy load carriage and manual handling. However, recent U.S. Army data showed that NCA soldiers (combat support and combat service support trades) had a higher musculoskeletal injury incidence or severity when compared with CA soldiers in some (19,20,30) but not all instances (2). It is acknowledged that these results are nuanced because musculoskeletal injury incidence and severity (e.g., limited duty days and medical discharge) are influenced by a variety of factors, including occupational exposure, physical fitness, sex and age distribution of the population, and access to medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with men, female soldiers are more likely to get injured in their lower limbs (5). It may be that their smaller size puts them at a higher risk of serious personal injury during weight training (6).…”
Section: Introductionmentioning
confidence: 99%